Dengue virus infection in a French traveller to the hilly region of Nepal in 2015: a case report - Gupta, Birendra Prasad (J Med Case Rep, 2016)
BACKGROUND: Dengue viral infections are known to pose a significant risk during travel to tropical regions, but it is surprising to find dengue transmission in the hilly region of Nepal, which is over 1800mtr above sea level. CASE PRESENTATION: A 43-year-old Caucasian female traveler from France presented with fever and abdominal pain following a diarrheal illness while visiting the central hilly region of Nepal. Over the course of 9 days, she developed fever, body aches, and joint pain, with hemorrhagic manifestation. She was hospitalized in India and treated with supportive care, with daily monitoring of her platelets. An assessment by enzyme-linked immunosorbent assay showed that she was positive for dengue non-structural protein 1. Upon her return to France, dengue virus was confirmed by reverse transcriptase-polymerase chain reaction. CONCLUSION: The district where this dengue case was reported is in the hilly region of Nepal, neighboring the capital city Kathmandu. To the best of our knowledge, there has previously been no dengue cases reported from the district. This study is important because it aims to establish a potential region of dengue virus circulation not only in the tropics, but also in the subtropics as well, which in Nepal may exceed elevations of 1800mtr. This recent case report has raised alarm among concerned health personnel, researchers, and organizations that this infectious disease is now on the way to becoming established in a temperate climate.